AS . biuletyn pism związkowych i zakładowych, no. 13, 1981 - NSZZ "Solidarność" Agencja Prasowa z siedzibą w MKZ "Mazowsze", [ed. Seweryn Blumsztajn et al.] (NSZZ "Solidarność" Agencja Prasowa, 1981)
Creation and circulation: Publication contains reprints of trade union documents and articles from the trade union press.